Startup for Organizing Sports Events: Conceptualization Based on the BMC Model - rabani Kheirallah, Moaz eddine; ben aissa, saber (sports creativity, 2024)
The study discusses the establishment of a startup company for organizing sports events using the Business Model Canvas (BMC). It highlights the importance of the idea as a fundamental driver for any project and the necessity of innovation in startups to achieve rapid growth despite the high risks of failure. The main conclusions emphasize the need to focus on projects and startups in the sports field as it represents a fertile economic ground, and to encourage startups through financial and administrative support and the provision of business incubators. The study also recommends training entrepreneurs to use the BMC and allocating resources to develop innovative business models, increasing awareness of the benefits of sports events to the local economy and society, and finally supporting research and development to enhance collaboration between universities and institutions and to innovate new solutions